2007
DOI: 10.1063/1.2772664
|View full text |Cite
|
Sign up to set email alerts
|

Thermally driven defect formation and blocking layers at metal-ZnO interfaces

Abstract: The authors used depth-resolved cathodoluminescence spectroscopy and current-voltage measurements to probe the temperature-dependent formation of native point defects and reaction layers at metal-ZnO interfaces and their effect on transport properties. These results identify characteristic defect emissions corresponding to metal-Zn alloy versus oxide formation. Au alloys with Zn above its eutectic temperature, while Ta forms oxide blocking layers that reduce current by orders of magnitude at intermediate tempe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
31
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 13 publications
1
31
0
Order By: Relevance
“…Staged annealing of metalÀZnOð0 0 01Þ contacts produces even more dramatic changes in subsurface defect and contact behavior [15]. Fig.…”
Section: Temperature-dependent Defect Formation and Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Staged annealing of metalÀZnOð0 0 01Þ contacts produces even more dramatic changes in subsurface defect and contact behavior [15]. Fig.…”
Section: Temperature-dependent Defect Formation and Barriersmentioning
confidence: 99%
“…The $2 eV feature that appears with 650 8C anneal corresponds with (b) a 100Â increase in I-V reverse current[15].…”
mentioning
confidence: 97%
“…[28][29][30] However, the structural and chemical integrity of the metal-nanowire interface play a key role in its transport properties. [1][2][3][4]27,31 Hence, it was necessary to thoroughly investigate the nature and Figure S2 and S3). The structural investigations showed the Au-ZnO nanowire interface is clean, flat, ordered and intimate, an ideal test bed to develop a fundamental understanding of the intrinsic electrical properties of particle-nanowire contacts.…”
mentioning
confidence: 99%
“…8 Previous ZnO surface studies revealed the importance of surface adsorbates, near-interface native defects, and thermally induced interface chemical interactions at metal/ZnO contacts. 3,9,10 Stabilization mechanisms of Zn͑0001͒-or O͑0001͒-terminated faces are still controversial, yet few experimental studies compare them. 11 Differences between hydrothermal ZnO polar surfaces were ascribed to surface band bending induced by spontaneous polarization, 12 while melt-grown ZnO exhibits only a small difference in band bending.…”
mentioning
confidence: 99%